Implementasi Metode Pembelajaran Inside-Outside Circle Dalam Meningkatkan Hasil Dan Ketuntasan Belajar Siswa Pada Mata Pelajaran Tik Kelas VIII Smp N 2 Batang - Arbiyanti, Yossi Norma; Suryono, Suryono (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
The aims of the study are to know how much improving learning outcomes of student in ICT learning with the implementation of Inside-outsdie Circle methods, to know how much the changes increase mastery learning of student, subsequent to the learning process improvement using Inside-outside Circle methods. This type of research is experimental, while the design of the study is a quasi experimental design model pretest-posttest control group design. Sampling was done by random sampling techniques, students of class VIII C as a experimental class and class VIII D as the control class. The results showed that the mean score of pretest class VIII C (experimental class) 57.22 and the mean score of posttest was 75.09, it meant that the students’ achievement was improved by 17.87. As for the class VIII D (control class) the mean score of pretest was 54.11 and the posttest mean score was 67.50, it meant that it was improved by 13.39. Percentage of mastery learning showed 54% of students completed KKM in class VIII C (experimental class) and 19% of students completed KKM in class VIII D (control class), percentage mastery learning of students achievement was improved by 35%. Based on the explanation above, it can be concluded that the learning Inside-outside Circle (IOC) methods can improve outcomes and mastery learning of students on ICT in class VIII SMP N 2 Batang.